HUBUNGAN SELF-REGULATED LEARNING DENGAN PROKRASTINASI AKADEMIKPADA MAHASISWA PROGRAM STUDI PENDIDIKANTEKNIK BANGUNANJURUSAN TEKNIK SIPILUNIVERSITAS NEGERI PADANG - 2192-2200 , Jeffry (CIVED, 2018)
Abstract—This research is motivated by the high prevalence of academic procrastinator behavior amongstudents of Building Engineering Education Study Program. Good learning independence and discipline are needed to help students manage their time and control themselves in learning process to avoid the academic procrastination.This research aims to reveal the relationship between self-regulated learning andacademic procrastination ofClass of 2013 students of Building Engineering Education Program in Civil Engineering Department of the State University of Padang. The sampleof this research was 72 students taken by using total sampling technique. Data analysis techniques used are: 1) Description analysis, 2) Analysis requirements test, and 3) Test of hypothesis. The result showed that there is a negative and significant relationshipbetweenself-regulated learning and academic procrastination of Class of 2013 students of Building Engineering Education Program in Civil Engineering Department of the State University of Padang, with 95% confidence level. This can be derived from the correlation coefficient value of 0.534, means that the relationship lies in moderate category.